IMPLEMENTASI KEBIJAKAN PENDIS TENTANG APLIKASI ARD DI MTS SE-KECAMATAN PEKUNCEN KABUPATEN BANYUMAS - Nina Asrie (STAI Sufyan Tsauri Majenang, 2020)
A leader in an institution or organization will continue to wrestle with a decision that must be taken. Every policy that he (a leader) takes, must be considered carefully for the survival of the institution. There are many new breakthroughs to support the performance of members of an institution, sometimes policy changes often occur due to the opening of some weaknesses of the policy that has been taken by the leader. Government policy in the implementation of ARD applications, is a new breakthrough. Pros and cons are also expressed in many ways by those who use them, educators for example. Along with the pros and cons in implementing the Digital Rapot Application there are also many solutions. But whether or not a leader is good is not only in terms of what policies he takes. But a good leader will take the policy as needed rather than not taking the policy at all.